Dystopien im fortgeschrittenen Englischunterricht: Station Eleven und The Wall - Hohwiller, Peter (Impulsgeber Fremdsprachen. Best Practice und Diskussionen aus der Tagung des "Gesamtverbands Moderne Fremdsprachen Bayern")

Great Britain in nine short stories

Praktiken, Diskurse und ihr materieller Zusammenhang. - Langer, Antje; Ott, Marion (Erziehungswissenschaftliche Subjektivierungsforschung)

Wahrnehmung und Effekte elterlichen Feedbacks auf die Lesemotivation und -leistung von Grundschulkindern. Vortrag im Rahmen des Symposiums „Lernen durch Feedback von Lehrpersonen, Eltern und Schüler:innen“ (Sebastian Röhl & Fabian Hoya) auf der 12. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung als Schlüssel für gesellschaftliche Herausforderungen: Interdisziplinäre Beiträge aus der Bildungsforschung“ - Knickenberg, Margarita; Hoya, Fabian; Hellmich, Frank

Determinanten für prosoziales Verhalten und Einstellungen von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf. Vortrag auf der 12. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung als Schlüssel für gesellschaftliche Herausforderungen: Interdisziplinäre Beiträge aus der Bildungsforschung“ - Löper, Marwin Felix; Hellmich, Frank

Wesensattribute Gottes in der Theologie Sayf ad-Dīn al-Āmidīs - Husic, Ahmed

Lie groups of real analytic diffeomorphisms are L^1-regular - Glöckner, Helge (Nonlinear Analysis)
Let $M$ be a compact, real analytic manifold and $G$ be the Lie group of all real-analytic diffeomorphisms of $M$, which is modelled on the (DFS)-space ${\mathfrak g}$ of real-analytic vector fields on $M$. We study flows of time-dependent real-analytic vector fields on $M$ which are integrable functions in time, and their dependence on the time-dependent vector field. Notably, we show that the Lie group $G$ is $L^1$-regular in the sense that each $[\gamma]$ in $L^1([0,1],{\mathfrak g})$ has an evolution which is an absolutely continuous $G$-valued function on $[0,1]$ and smooth in $[\gamma]$. As tools for the proof, we develop several new results concerning $L^p$-regularity of infinite-dimensional Lie groups, for $1\leq p\leq \infty$, which will be useful also for the discussion of other classes of groups. Moreover, we obtain new results concerning the continuity and complex analyticity of non-linear mappings on open subsets of locally convex direct limits.

Meine Schwangerschaft - so individuell wie ich! - Schneider, Tamara; Weber, Julia

Kinderlyrik als soziale Praxis am Beispiel von Arne Rautenbergs Lyrikbänden Mut ist was Gutes (2023) und Sekundenfrühling (2023) - Jagdschian, Larissa Carolin (Arne Rautenbergs und die (Kinder-)Lyrik der Gegenwart)

Das ‚andere‘ Europa der Schriftsteller. Ideen, Netzwerke und Schreibweisen des antiliberalen Europa-Diskurses in Deutschland und Österreich (1918–1934) - Heise, Tillmann

Symmetry Preservation in Swarms of Oblivious Robots with Limited Visibility - Gerlach, Raphael; von der Gracht, Sören; Hahn, Christopher; Harbig, Jonas; Kling, Peter (28th International Conference on Principles of Distributed Systems (OPODIS 2024))
In the general pattern formation (GPF) problem, a swarm of simple autonomous, disoriented robots must form a given pattern. The robots' simplicity imply a strong limitation: When the initial configuration is rotationally symmetric, only patterns with a similar symmetry can be formed [Yamashita, Suzyuki; TCS 2010]. The only known algorithm to form large patterns with limited visibility and without memory requires the robots to start in a near-gathering (a swarm of constant diameter) [Hahn et al.; SAND 2024]. However, not only do we not know any near-gathering algorithm guaranteed to preserve symmetry but most natural gathering strategies trivially increase symmetries [Castenow et al.; OPODIS 2022]. Thus, we study near-gathering without changing the swarm's rotational symmetry for disoriented, oblivious robots with limited visibility (the OBLOT-model, see [Flocchini et al.; 2019]). We introduce a technique based on the theory of dynamical systems to analyze how a given algorithm affects symmetry and provide sufficient conditions for symmetry preservation. Until now, it was unknown whether the considered OBLOT-model allows for any non-trivial algorithm that always preserves symmetry. Our first result shows that a variant of Go-to-the-Average always preserves symmetry but may sometimes lead to multiple, unconnected near-gathering clusters. Our second result is a symmetry-preserving near-gathering algorithm that works on swarms with a convex boundary (the outer boundary of the unit disc graph) and without holes (circles of diameter 1 inside the boundary without any robots).
Keywords: Swarm Algorithm; Swarm Robots; Distributed Algorithm; Pattern Formation; Limited Visibility; Oblivious

Reconsidering the Human Condition: An Arendtian Perspective on Earth, Education, and Political Subjectivity in Times of Environmental Crisis - Robaszkiewicz, Maria Anna (Rethinking Responses to Political Crisis and Collapse: Hannah Arendt, Edith Stein, Rosa Luxemburg, and Simone Weil)

Effect of Compression Rate and Pore Size Distribution on the Compression Behavior of Additively Manufactured Bio-inspired Fe3Si Microporous Material - Pramanik, Sudipta; Mileaege, Dennis; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)

„Power-Posen“ – Fakten, frisierte Daten, Forschungslyrik? Eine Unterrichtsreihe zu Praktiken und Darstellungsformen psychologischer Forschung - Scharlau, Ingrid; Patrzek, Justine; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Materialien zum Schreiben im Psychologieunterricht - Scharlau, Ingrid; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

A Systematic Review of Learning Opportunities within the Crowdworkers’ Workplace - Drechsler, Stephan; Harteis, Christian (Journal of Education and Learning)

"Und es hörten sie die Gefangenen" Eine biblische Gesangsstunde. Apg 16,23-34 (18.5.2025 - Kantate) - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Error estimates for full discretization by an almost mass conservation technique for Cahn--Hilliard systems with dynamic boundary conditions - Bullerjahn, Nils (arXiv)

Modeling reactive absorption in sandwich packings - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Proceedings of the Dechema/VDI Jahrestreffen Fluidverfahrenstechnik 2025)

Islam II - Paul, Jürgen; Schneider, Irene; Kokew, Stephan; Malik, Jamal; Schulze, Fritz; Günther, Sebastian; Schrode, Paula; Rebstock, Ulrich; Gharaibeh, Mohammad; Würsch, Renate; Rudolph, Ulrich; Reichmuth, Stefan; et al.